An analysis of students’ listening comprehension through video-based internet material (BBC) in second grade students of SMAN 4 Bandar Lampung in 2016-2017 - Prasetya, Yoga; Anggia, Helta (Universitas Mathla'ul Anwar Banten, 2019)
This research aims to apply BBC (British Broadcasting Cooperation) to students. BBC is one of broadcaster in Britain and it provides a website to learn. Its name is BBC Learning English and it shows many videos and the facilities to learn. The purpose of this research is to analyze the students’ listening comprehension. In this research, I used qualitative research. The kind of research was used to get information about phenomenon and an accident during the research. The method of this research was audio-visual method where students used their sight and hearing sense. Because BBC provided many videos, it was apt with this method. In here, students did not merely acquire the information from their hearing sense but they were helped by the picture and the accident. The result of this research showed that the improvement from first meeting to second meeting. The improvement happened in their comprehension. In the first meeting, six students can be said fail in the test. They wrote everything in the video but they could not comprehend the topic. In the second meeting, most of them caught the material well. The topic was comprehended extensively. Mostly, students could simply comprehend the material that I presented through BBC. Based on the fact in this research, they preferred to use this website than others. It stimulated them to learn. It is a proof that BBC could help them in the listening comprehension. It is not only about listening comprehension but students could learn grammar and vocabulary.